REPRESENTAÇÕES SOCIAIS SOBRE O SOFRIMENTO MENTAL E OS MODELOS DE TRATAMENTO PSIQUIÁTRICO: O OLHAR DOS FAMILIARESCUIDADORES E DOS TRABALHADORES EM SAÚDE MENTAL DE PONTA GROSSA – PR - Trentini, Fabiana Vosgerau (2011)
This thesis has as its object of study the social representations that family caregivers and mental health professionals have of the mental suffering and of the models of psychiatric treatment in the municipality of Ponta Grossa, PR. Ponta Grossa was, for almost forty years, the host city of the Franco da Rocha Psychiatric Hospital (HPFR). It opened in 1967 and ended its activities in 2004. From the 274 beds at the time of the closing of its doors, 260 had an agreement with the Sistema Único de Saúde – SUS (a public health system), and were destined to patients in mental suffering who lived in the twelve municipalities that make up the 3ª Regional de Saúde – PR. In order to replace the hospital-care model represented by the HPFR, in September 2006 the Centro de Atenção Psicossocial II – Transtorno Mental – CAPS II – TM was created, on the basis of the Federal Law no. 10.216, which prescribes the adoption of actions involving a psychosocial treatment model of socio-familial inclusion. From that time on, social actors directly involved in questions of mental illness and health – mainly family relatives of people in mental suffering and mental health professionals – have had to reconsider the model of psychiatric attention. In this thesis we present the results of a research whose aim was to identify the social representations of mental suffering and treatment by 04 caregivers who were in charge of individuals that lived the experience of internment in the HPFR, from 1979 to 1994, but now attend the CAPS, in view of the new policy of mental health support. The research also aimed at investigating the social representations of three professionals of the CAPS team and two mental health professionals who experienced the two therapeutic models in their everyday practice. We regard the caregivers and these two professionals as meaningful social subjects, for they intensely lived the hospital-centric model and, in the last four years, have experienced the changes under the aegis of the Psychiatric Reform. Changes and permanencies in relation to the social representation of the phenomenon called madness‟ are identified in the speech content of the family caregivers and professionals, which nevertheless emphasize certain ruptures brought about by the Psychiatric Reform.